2001
DOI: 10.1034/j.1399-0004.2001.590308.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational screening of the cationic trypsinogen gene in a large cohort of subjects with idiopathic chronic pancreatitis

Abstract: Several missense mutations, including R122H, N29I, K23R, A16V and D22G, in the cationic trypsinogen gene (PRSS1), have been associated with certain forms of hereditary pancreatitis (HP). Their occurrence in the idiopathic chronic pancreatitis (ICP) and whether novel mutations could be identified in PRSS1 remain to be further evaluated. These were addressed by the mutational screening of the entire coding sequence and the intronic/exonic boundaries of the PRSS1 gene in 221 ICP subjects, using a previously estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…In this study, the simple PRSS1 and PSTI genes ± the former is composed of only five exons encoding 247 amino acids 25 and the latter consists of only four exons encoding 79 amino acids 26 ± were subjected to our previously established DGGE analyses, which have been demonstrated to be both sensitive and efficient, as well as capable of detecting known mutations and identifying novel variants. 6,10,21 In contrast, it is not easy to perform a complete analysis of the CFTR gene, which consists of 27 exons encoding 1480 amino acids. 27 Indeed, to date, most of the relevant studies have investigated only a selected subset of the most common CFTR mutations in CP.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the simple PRSS1 and PSTI genes ± the former is composed of only five exons encoding 247 amino acids 25 and the latter consists of only four exons encoding 79 amino acids 26 ± were subjected to our previously established DGGE analyses, which have been demonstrated to be both sensitive and efficient, as well as capable of detecting known mutations and identifying novel variants. 6,10,21 In contrast, it is not easy to perform a complete analysis of the CFTR gene, which consists of 27 exons encoding 1480 amino acids. 27 Indeed, to date, most of the relevant studies have investigated only a selected subset of the most common CFTR mutations in CP.…”
Section: Discussionmentioning
confidence: 99%
“…The entire PRSS1 gene was sequenced in these patients. Only three patients had mutations, one with R122H and two patients with A16V [27] . A genetic background has also been investigated in patients with idiopathic juvenile chronic pancreatitis, a disease which closely mimics the clinical pattern of hereditary pancreatitis [28] .…”
Section: Cationic Trypsinogen Gene Mutations In Non-hereditary Pancrementioning
confidence: 98%
“…The most frequently observed SPINK1 mutations are N34S and P55S, occurring mainly in Europe and the USA. Many studies provide evidence for the relationship between N34S mutation and chronic pancreatitis of varied aetiology, with a frequency of approximately 9.7% [15,56,[69][70][71]. The mechanism combining SPINK1 p.N34S mutation with pancreatitis remains unexplained [71].…”
Section: Spink1mentioning
confidence: 99%
“…An asparagineisoleucine replacement at position 29 of cationic trypsinogen results in an increase in resistance to autolytic processes [55]. The A16V mutation is the third most frequent PRSS1 mutation with changeable penetration, most often in the group of patients with idiopathic pancreatitis [47,56]. The results of studies conducted by Nemoda [51] in 2006 confirmed that the A16V mutant protein, contrary to R122H and N29I, does not itself increase auto-activation of cationic trypsinogen; however, the stimulation of autoactivation by chymotrypsin C plays a role in chronic pancreatitis related with A16V mutation [51].…”
Section: Prss1mentioning
confidence: 99%